Impact of Target‐Mediated Elimination on the Dose and Regimen of Evolocumab, a Human Monoclonal Antibody Against Proprotein Convertase Subtilisin/Kexin Type 9 (PCSK9). (15th November 2016) - Gibbs, John P.; Doshi, Sameer; Kuchimanchi, Mita; Grover, Anita; Emery, Maurice G.; Dodds, Michael G.; Gibbs, Megan A.; Somaratne, Ransi; Wasserman, Scott M.; Blom, Dirk
Abstract: Understanding the pharmacokinetic (PK) and pharmacodynamic (PD) relationship of a therapeutic monoclonal antibody against proprotein convertase subtilisin/kexin type 9 (PCSK9) exhibiting target‐mediated drug disposition (TMDD) is critical for selecting optimal dosing regimens. We describe the PK/PD relationship of evolocumab using a mathematical model that captures evolocumab binding and removal of unbound PCSK9 as well as reduction in circulating low‐density lipoprotein cholesterol (LDL‐C). Data were pooled from 2 clinical studies: a single‐dose escalation study in healthy subjects (7‐420 mg SC; n = 44) and a multiple‐dose escalation study in statin‐treated hypercholesterolemic patients (14 mg weekly to 420 mg monthly [QM] SC; n = 57). A TMDD model described the time course of unbound evolocumab concentrations and removal of unbound PCSK9. The estimated linear clearance and volume of evolocumab were 0.256 L/day and 2.66 L, respectively, consistent with other monoclonal antibodies. The time course of LDL‐C reduction was described by an indirect response model with the elimination rate of LDL‐C being modulated by unbound PCSK9. The concentration of unbound PCSK9 associated with half‐maximal inhibition (IC50 ) of LDL‐C elimination was 1.46 nM. Based on simulations, 140 mg every 2 weeks (Q2W) and 420 mg QM were predicted to achieve a similar time‐averaged effect of 69% reduction in LDL‐C in patients on statin therapy, suggesting that an approximate 3‐fold dose increase is required for a 2‐fold extension in the dosing interval. Evolocumab dosing regimens of 140 mg Q2W or 420 mg QM were predicted to result in comparable reductions in LDL‐C over a monthly period, consistent with results from recently completed phase 3 studies.